Financial Feasibility of Arabica Coffee Plantation Business Through Partnership Pattern in Solok Regency, West Sumatra - Faidil Tanjung; Dwi Evaliza; Rafnel Azhari (Universitas Andalas, 2022)
Lembah Gumanti District has the largest area of Arabica coffee in Solok Regency, with a production of 2588.8 tons in 2019. Some problems farmers face in developing Arabika coffee farming include a lack of knowledge of cultivation techniques and low selling price of coffee (cherry) beans at the farm gate. The Solok Radjo Cooperative emerged to solve farmers' problems and is willing to help develop Arabica coffee plantations in partnership. This study aims to: (1) describe the implementation of partnerships in Arabica coffee farming and (2) analyze the feasibility of arabica coffee farming with partnership pattern. A survey method was used involving 40 sample farmers selected using simple random sampling. Data analysis was carried out qualitatively to determine the implementation and benefits obtained by the partnering parties (farmers and Solok Radjo Cooperative). Quantitative analysis is intended to determine the financial feasibility of developing Arabica coffee with a partnership pattern. In the partnership system, the Solok Radjo Cooperative provides farmers assistance to use superior seeds, socialization of Arabica coffee cultivation and harvesting techniques, and willingness to buy coffee beans (cherry) from farmers with higher prices than local collectors. The benefit obtained by the Solok Radjo Cooperative is the guaranteed supply of Arabica coffee production with better quality. Arabica coffee plantation business through this partnership is feasible with a Net BC ratio of 2.43.